Предмет: Алгебра,
автор: yvarovnikita26
Упростить выражение д)6(с+1)-6с-5; е)19у+2(3-4у)+11у; ж)21х-7-4(9х+3); з)33-8(11b-1)-2b.
Ответы
Автор ответа:
0
д)6(с+1)-6с-5=6с+6-6с-5=6-5=1
е)19у+2(3-4у)+11у=19у+6-8у+11у=11у+11у+6=22у+6
ж)21х-7-4(9х+3)=21х-7-36х-12=-15х-19
з)33-8(11b-1)-2b=33-88b+8-2b=41-90b
е)19у+2(3-4у)+11у=19у+6-8у+11у=11у+11у+6=22у+6
ж)21х-7-4(9х+3)=21х-7-36х-12=-15х-19
з)33-8(11b-1)-2b=33-88b+8-2b=41-90b
Похожие вопросы
Предмет: География,
автор: oleh2008kasyanenko
Предмет: Обществознание,
автор: Аноним
Предмет: Химия,
автор: Аноним
Предмет: Геометрия,
автор: Аноним